Pola Asuh Otoritatif dengan Kemandirian Anak Down Syndrome dalam Melakukan Activity Daily Living - Evania Yanasari Ritto; Hartanti Hartanti; Mary Philia Elisabeth (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2020)
Abstract— The goal of this research was to find out the relation between authoritative parenting and the independence of down syndrome children in doing activity daily living. The participants in this study were 33 parents who had down syndrome children. The sampling technique in this study was conducted by purposive technique. Data collection techniques were carried out by distributing questionnaires for the Parenting Style Dimension Questionnare (PSDQ) and Functional Indpendence Measure for Children (WeeFIM). The results of hypothesis testing using Pearson correlation were found a significantly positive between authoritative parenting and the independence of down syndrome children in performing daily living activities (r = 0.498 <0.05; r = 0.498). Based on the results of the crosstab, significant associations were found between parents' education, children's age, parents' thoughts about the child's condition, parents' feelings of having down syndrome children, parental treatment to improve children's abilities, and parental treatment of the child's condition with significant associations with independence of down syndrome children in doing activity daily living Keywords : authoritative parenting, independence, down syndrome, activity daily living Abstrak—Penelitian ini bertujuan untuk mengetahui hubungan antara pola asuh otoritatif dengan kemandirian anak down syndrome dalam melakukan activity daily living. Partisipan dalam penelitian ini sebanyak 33 orang tua yang mempunyai anak down syndrome. Teknik pengambilan sampel dalam penelitian ini dilakukan dengan teknik purposive. Teknik pengambilan data dilakukan dengan membagikan angket Parenting Style Dimension Questionnare (PSDQ) dan Functional Indpendence Measure for Children (WeeFIM). Hasil uji hipotesis menggunakan korelasi pearson dan ditemukan hubungan positif yang signifikan antara pola asuh otoritatif dengan kemandirian anak down syndrome dalam melakukan activity daily living (r=0,498 < 0,05; r = 0,498). Berdasarkan hasil crosstab ditemukan asosiasi signifikan antara pendidikan akhir orang tua, usia anak, pikiran orang tua mengenai kondisi anak, perasaan orang tua memiliki anak down syndrome, perlakuan orang tua untuk meningkatkan kemampuan anak, dan perlakuan orang tua terhadap kondisi anak memiliki asosiasi signifikan dengan kemandirian anak down syndrome dalam melakukan activity daily living. Kata kunci : pola asuh otoritatif, kemandirian, down syndrome, activity daily living